A review of plant anti-nutritional factors in animal health and production: The classification, biological properties, and the passivation strategy - Fariborz Khajali; Fariba Rafiei (Journal of Agriculture and Food Research)
This review provides insights into the classification and biological properties of plant secondary metabolites (PSMs) in farm animal nutrition. It serves as a single reference dealing with a broad range of PSMs affecting animal health and performance. PSMs have been classified in seven main groups including glycosides, alkaloids, phenolic compounds, phytic acid, non-starch polysaccharides, lectins, and enzyme inhibitors. The occurrence and anti-nutritional effects of PSMs, which are associated with plant, environment, animal, and processing factors, have been discussed. Methods for neutralizing PSMs have also been reviewed. Besides, the review provides insights into the adaptations to PSMs by farm animals through modulations in the gut microbiome. Such findings may be exploited to develop novel feed additives. This review also reveals beneficial properties of PSMs and such beneficial attributes can be used to promote animal and human health.